Improving The Quality Of Islamic Boarding Schools Through The Management Of Santri Pondok Pesantren Nurul Huda - Inayati, Mahfida; Quraisy, Sherly; Mulyadi, Mulyadi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
Improving the quality of an Islamic boarding school is an important thing that must continue to be updated in line with current developments. This can be done by strengthening the management of students, the process carried out is guided by competency learning, so that students have competitiveness and become qualified in terms of learning and quality. implementation of values in life. The balance of students' knowledge is balanced in understanding Salafi science and also technological knowledge with the management of Islamic boarding schools such as activity programs, extra-curricular programs and also learning methods and strategies for improving the morals of students, so by managing the management of Nurul Huda Islamic boarding school students, the quality of Islamic boarding schools can be improved.